IDENTIFIKASI RESPON PESERTA DIDIK TERHADAP E-LKPD INTERAKTIF FISIKA BERBANTUAN LIVE WORKSHEETS POKOK BAHASAN PENGUKURAN - Syafira Syaifatul Choiroh; Sri Handono Budi Prastowo; Lailatul Nuraini (JURNAL PEMBELAJARAN FISIKA, 2022)
The learning process can run well when there is interaction or reciprocity between teachers and students. One of the reciprocity between students and teachers is the response. Therefore, the response becomes one of the important components in the learning process. One of the requirements for a learning process to run smoothly and achieve maximum learning objectives is the response of students. The purpose of this study was to describe student responses to the use of interactive physics E-LKPD assisted by worksheets in measurement subjects. This research is a type of quantitative descriptive research with data collection techniques using student response questionnaires which are distributed after using the interactive physics E-LKPD assisted by LKS for measurement subjects. The sample in this study was 30 students of class X SMA Negeri Ambulu Jember Regency. The results of student responses after using interactive physics E-LKPD assisted by Live Worksheets are based on indicators, namely: the format indicator is 81%, the relevance indicator is 82%, the confidence indicator is 73%, and the interest indicator is 75%. The average result of student responses from all statements is 79% which means it is in the good or positive category.